Reproductive success of the wood warbler Phylloscopus sibilatrix varies across Europe. (7th September 2022) - Maag, Nino; Burgess, Malcolm D.; Maziarz, Marta; Lüpold, Shannon; Mallord, John W.; Broughton, Richard K.; Cristinacce, Andrew; Arlettaz, Raphaël; Carlotti, Sandro; Castello, Joan; Davis, Tony; Gerber, Michael; et al.
Abstract : Differences in population trends across a species' breeding range are ultimately linked to variation in demographic rates. In small songbirds, demographic rates related to fecundity typically have strong effects on population trends. Populations of a forest songbird, the wood warbler Phylloscopus sibilatrix, have been declining in many but not all regions of the European breeding range. We investigated if clutch size, hatching rate, nest survival and number of fledglings vary across Europe, and if nest survival is related to differences in the regionally dominant nest predator class (birds versus mammals). From 2009 to 2020, we monitored 1896 nests and used cameras at a subsample of 645 nests in six study regions: the United Kingdom (mid‐Wales, Dartmoor, the New Forest), Germany (Hessen), Switzerland (Jura mountains) and Poland (Białowieża National Park). Number of fledglings was lowest in the New Forest (1.43 ± CI 0.23), intermediate in Jura (2.41 ± 0.31) and Białowieża (2.26 ± 0.24) and highest in mid‐Wales (3.02 ± 0.48) and Dartmoor (2.92 ± 0.32). The reason for low reproductive success in the New Forest, Jura and Białowieża was low nest survival, and large clutch sizes in Białowieża did not compensate for high nest losses. High reproductive success in mid‐Wales and Dartmoor was due to high nest survival and large clutch sizes. Overall predation rates were similar everywhere despite variation between the regions in the dominant nest predator class. Unsuccessful nests in mid‐Wales were mainly predated by birds; in Dartmoor, the New Forest, Hessen and Jura similarly by birds and mammals; and in Białowieża exclusively by mammals. Regional reproductive success does not match the population trends recently reported for the wood warbler in the six study regions (i.e. high reproduction ≠ positive trend). Annual survival may be a decisive factor, but it is difficult to quantify for a nomadic species such as the wood warbler that rarely returns to the same breeding locations.